Interacción funcional entre burocracia y asociaciones en las estructuras organizacionales - Prado-Chinga, Alberto Efraín; Macias-Loor, Jazmina Mariela (Editorial Grupo AEA, 2026)
This article analyzes the functional interaction between bureaucracy and associations within organizational structures. Associations, such as those of farmers, merchants, and livestock producers, act as key players representing collective interests within a structured bureaucracy, facilitating decision-making and the creation of more efficient policies. Through a theoretical analysis, the study examines the collaborative dynamics that emerge from these interactions, highlighting how associations overcome bureaucratic barriers and optimize organizational processes. This research offers a new perspective on the ability of associations to influence organizational management, promoting a framework of functional collaboration within public and private institutions.